Análisis de la planta turística, oferta ocio y recreación en el cantón La Maná. - Andrade Tapia, Oscar Alexis (2020)
The canton of La Maná has a diversity of tourist plants, which contributes to the economic activity of the place, this research project aimed to analyze the tourist plant, leisure and recreation offer of the canton, in order to obtain updated data. For the elaboration of the study, the respective bibliographic review in books and documents was made in order to obtain a situational and tourist diagnosis, where it was demonstrated that the main economic activity comes from the cattle raising and agriculture being these the main axes of economic development in the canton, It was also found that part of the population is dedicated to tourism, so it was necessary to identify each of the recreational activities offered by the canton. This was done through the use of methods and techniques that provided current information on the sites and recreational establishments, highlighting shortcomings and the lack of interest in the administration and care of the tourist facilities by government agencies. Likewise, to know the tourist plant we based on the cadastre of the Ministry of Tourism of the year 2020, where a current diagnosis of the existing spaces of leisure and recreation in the canton was obtained, here was found only 5 establishments that are dedicated to the provision of services of recreation, so by means of field trips it was possible to be demonstrated that the cadastre is incomplete and in addition several establishments do not have the classification that corresponds to them. There are sites and establishments dedicated to tourism, leisure and recreation so according to this classification we have; 13 tourist complexes, 26 squares and parks, 12 natural tourist attractions, 4 cultural tourist attractions, 11 cultural sites, 3 bars and 8 discos, these sites and establishments are promoters of the leisure and recreaction activity in the cantón. As a final result of the project, a catalogue was made which contains the sites and establishments that were inventoried and classified, since those that are in optimum condition in terms of service and infrastructure were considered so that the catalogue can serve as an information tool for leisure and recreation spaces. In addition, recommendations were established to promote improvements in the social, cultural and tourist areas in the canton of La Maná.